2019
DOI: 10.1111/jocs.14038
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers associated with 30‐day readmission and mortality after pediatric congenital heart surgery

Abstract: Objectives Novel cardiac biomarkers serum (suppression of tumorigenicity [ST2]) and Galectin‐3 may be associated with an increased likelihood of important events after cardiac surgery. Our objective was to explore the association between pre‐ and postoperative serum biomarker levels and 30‐day readmission or mortality for pediatric patients. Methods We prospectively enrolled pediatric patients <18 years of age who underwent at least one cardiac surgical operation at Johns Hopkins Children's Center from 2010 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Meanwhile, Parker et al [ 26 ] found that ST2 and Galectin-3, unlike BNP, are not developmentally regulated and therefore not confounded by age. Furthermore, the biologic and analytic variability of ST2 is much lower than BNP, suggesting that ST2 levels may be better in risk stratification and prognostication.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Parker et al [ 26 ] found that ST2 and Galectin-3, unlike BNP, are not developmentally regulated and therefore not confounded by age. Furthermore, the biologic and analytic variability of ST2 is much lower than BNP, suggesting that ST2 levels may be better in risk stratification and prognostication.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48] Kogon and colleagues identified ethnicity, pre-operative failure to thrive, and post-operative length of stay as significant predictors of readmission. 2 Others reported arrhythmia, post-pericardiotomy syndrome, and infectious complications were the most common readmission diagnoses, 46 or they found infectious complications to be a common readmission diagnosis in children who had previously undergone Norwood palliation for hypoplastic left heart syndrome. 47 The most common variables used to determine the risk of adverse outcomes following paediatric congenital heart surgery are based on the estimated risk of mortality following surgery, as defined by The Society of Thoracic Surgeons Congenital Heart Surgery Database Mortality Risk Model.…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al 28 conducted a cohort study with 162 patients aged 18 years who had undergone cardiac surgery between 2010 and 2014. They found that 12.9% of the patients experienced readmission or death during the first 30 days after discharge.…”
Section: Discussionmentioning
confidence: 99%